2019
DOI: 10.2147/oajsm.s198500
|View full text |Cite
|
Sign up to set email alerts
|

<p>Musculoskeletal injuries in real tennis</p>

Abstract: Introduction: Real tennis is a growing, unique, and well-established sport. To date, there has been no epidemiological data on real tennis injuries. The primary aim of this retrospective study is to record the incidence and document any trends in real tennis musculoskeletal injuries, so as to improve injury awareness of common and possibly preventable injuries. Methods: A surveillance questionnaire e-mailed to 2,036 Tennis & Rackets Association members to retrospectively capt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 11 publications
0
2
0
1
Order By: Relevance
“…One benefit of the new FAIMS-Pro device was the ability to quickly switch between different CVs within a single method (dwell time ~25 ms). 29 We and others previously showed that combining multiple CVs within a single run or between runs improved whole proteome coverage. [11][12][13] Therefore, we next tested if increasing the number of CVs within a single method (multi-CV method) increased the unique peptide identifications for nonderivatized (label-free) and derivatized (TMT and TMTpro) samples.…”
Section: Resultsmentioning
confidence: 99%
“…One benefit of the new FAIMS-Pro device was the ability to quickly switch between different CVs within a single method (dwell time ~25 ms). 29 We and others previously showed that combining multiple CVs within a single run or between runs improved whole proteome coverage. [11][12][13] Therefore, we next tested if increasing the number of CVs within a single method (multi-CV method) increased the unique peptide identifications for nonderivatized (label-free) and derivatized (TMT and TMTpro) samples.…”
Section: Resultsmentioning
confidence: 99%
“…prevención general. El programa de prevención es la adaptación realizada por Finch (2006) del modelo de Van Mechelen et al (1992) con la incorporación de los conceptos del comportamiento en la toma de riesgos y el cumplimiento del individuo de los factores limitantes en la prevención de lesiones deportivas aportándole eficacia, eficiencia y cumplimiento al proceso de prevención (Van Tiggelen et al, 2008;Pas, Bodde, Kerkhoffs, Pluim,, Tiemessen, Verhagen & Gouttebarge, 2018;Fu, Ellenbecker, Renstrom, Windler & Dines, 2018;Humphrey, Humphrey, Greenwood, Anderson, Markus & Ajuied, 2019).…”
Section: Fundamentos Generales De Un Programa Preventivounclassified
“…The repetitive nature of these actions, without adequate healing and recovery time, predominantly contributes to these injuries (8). Research in this domain has been extensive, with studies such as those by Kaiser et al ( 9), Humphrey et al (10), Talha et al (11), Toma et al (12), and Moussa et al (13) providing valuable insights into the prevalence and nature of musculoskeletal injuries among tennis and other sports players. Kaiser et al highlighted the distribution of acute injuries in recreational tennis players, noting a significant portion of lower extremity injuries (9).…”
Section: Introductionmentioning
confidence: 99%
“…Kaiser et al highlighted the distribution of acute injuries in recreational tennis players, noting a significant portion of lower extremity injuries (9). Humphrey et al reported on the injuries sustained by amateur and professional real tennis players, indicating a mix of gradual and sudden onset injuries across different limbs (10). Talha et al focused on table tennis players, finding a high incidence of musculoskeletal pain, particularly in the spine and limbs (11).…”
Section: Introductionmentioning
confidence: 99%